The Specification of the Regime Structure in Turkish Economy with MS-VAR - (:unkn) unknown (BILGESEL YAYINCILIK SAN & TIC LTD, 2013)
The Specification of the Regime Structure in Turkish Economy with MS-VAR The structural changes in Turkey's economy which began in 1980, ended at the beginnings of 1990 by the completion of the process, then stepped in a term during which economy is frequently faced to face crises with the effect of internal and external shocks and serious fluctuations is observed. In this term, the general situation of economy can be explained shortly as spiral of high real interest rates, entries of hot money, low value of national currency as a result of frequent and huge devaluations in the value of national currency. Since 2002, transition to the strong economy program has been put into practice as a result of crises with the effect of crises experienced at the end of 1990 and at the beginning of 2000. Short summary of this term points out that various structures are the case in Turkish economy. The aim of this paper is to present the regime structure of Turkey's economy in the period from the beginning of 1990 to 2007, in other words, determination of regime change periods. In this study, Markov switching vector autoregressive (MS-VAR) models are used in determining the regime structure. Analyses are done for the period 1992:01-2007:03 by using current account, GDP growth rate, ratio of import coverage by export and interest rate series which are important and continuously observed macroeconomic variables and findings of this analyze exhibit the existence of three different regimes in this time period. This study's findings, especially related to the particular characteristics of pre-crisis period, contribute to reduce uncertainty and guide for decision makers in money and financial markets.
Keywords: MS-VAR; Regime Switching; Turkish Economy; MS-ADF Test; Impulse-Response Analysis; BUSINESS-CYCLE PHASES; EXCHANGE-RATE; SWITCHING MODELS; TIME-SERIES; MARKOV